Clinical characteristics, treatment patterns and adherence in patients with asthma on multiple inhaler triple therapy: a review of findings. Issue 11 (2nd November 2022) - Cazzola, Mario; Calzetta, Luigino; Rinaldi, Barbara; De Novellis, Vito; Rogliani, Paola; Matera, Maria Gabriella
ABSTRACT: Introduction: The value of treating asthma with the triple regimen of inhaled corticosteroid (ICS), long-acting β2 -agonist (LABA), and long-acting muscarinic antagonist (LAMA) delivered using multiple inhalers (MITT), or a single inhaler (SITT) is supported by a growing body of evidence, although research is still limited regarding the use of MITT. Areas covered: Clinical characteristics, treatment patterns, disease burden, and persistence/adherence associated with MITT use in asthma. The MEDLINE database was searched to identify references from inception until October 2022. Expert opinion: The use of MITT is not very frequent in asthma patients, although it improves lung function and reduces the incidence of severe exacerbations. This may be due to existing concerns about using different devices on adherence and persistence to treatment, with a negative influence on outcomes, and to the fear that the patient will discontinue ICS/LABA but not LAMA. Nevertheless, although the current trend favors the SITT approach, some physicians may be induced to prescribe MITT over SITT because it allows the titration of individual components of triple therapy to be increased or decreased. Therefore, there is an evident need for pragmatic real-life studies to document when to prefer SITT and when MITT should be used.